IN THE CONTEXT OF STRATEGIC MANAGEMENT, EFFICIENCY ANALYSIS OF REGIONAL COURTS OF APPEAL IN TÜRKİYE (Third Sector Social Economic Review, 2023)
In the context of strategic performance management, in this study the efficiency of regional courts of appeal in Türkiye is analysed. The number of judges, the number of administrative staff, the number of cases and the budget were taken as inputs and the number of case decisions were taken as output from the data of the fifteen regional courts of appeal covering the year 2021. Data envelopment analysis (DEA), bootstrapped DEA and k-means cluster analysis were performed. In the first stage DEA (BCC model) findings, it was seen that eight courts were efficient and seven were inefficient. In order to eliminate the bias of the DEA, bootstrapped DEA was performed in the second stage. In the results of the second stage, it was determined that the efficiency of Istanbul, which is the largest regional court of appeal, remained relatively low efficiency. This finding indicates that bootstrapped DEA gives more consistent results in court efficiency. In the third stage, k-means cluster analysis was carried out by considering the number of cases and efficiency scores of the courts. It was observed that the courts included in the analysis were gathered in three clusters, the first cluster had low number of cases and high efficiency scores, the second group had low efficiency scores despite the low number of cases, and the third group had high number of cases and high efficiency scores. The obtained findings are compatible with the literature. Moreover, as far as we know, this is the first study in which both the administrative efficiency of the justice system in Türkiye is examined and the bootstrap DEA is used in judicial efficiency. In this sense, it is expected to contribute to the literature.
Keywords: strategic performance management; judicial efficiency analysis; bootstrapped DEA; k-means clustering